2006
DOI: 10.1002/ijc.22190
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of EGFR mutation screening in pleural fluid to predict the clinical outcome of gefitinib treated patients with lung cancer

Abstract: The importance of epidermal growth factor receptor (EGFR) gene mutation has been recognized in nonsmall cell lung cancer (NSCLC), requiring the standardization of mutation screening system including the kind of samples. Here, we examined the EGFR mutation status in 61 pleural fluid samples from NSCLC cases using direct sequencing, nonenriched PCR, mutant-enriched PCR and peptide nucleic acid-locked nucleic acid (PNA-LNA) PCR clamp assay. The mutant-enriched PCR assay detected 16 mutant cases. Among them, the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 29 publications
4
77
0
Order By: Relevance
“…Thus, the advantages of the PNA-clamp SmartAmp2 assay will improve the efficacy of EGFR-TKI and other treatments and improve the quality of life of patients by minimizing the waiting time until the initiation of the appropriate treatment. Recently, the presence of EGFR mutations in plasma, serum, and pleural effusion has become a focus of interest (31)(32)(33)(34). The PNA-clamp SmartAmp2 assay may also contribute to the development of mutant DNA detection methods in these specimens, which contain extremely small amounts of mutant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the advantages of the PNA-clamp SmartAmp2 assay will improve the efficacy of EGFR-TKI and other treatments and improve the quality of life of patients by minimizing the waiting time until the initiation of the appropriate treatment. Recently, the presence of EGFR mutations in plasma, serum, and pleural effusion has become a focus of interest (31)(32)(33)(34). The PNA-clamp SmartAmp2 assay may also contribute to the development of mutant DNA detection methods in these specimens, which contain extremely small amounts of mutant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Such a technique has been applied to search for K-Ras mutations in various tumour samples (Sun et al, 2002;Chen et al, 2004;Taback et al, 2004;Däbritz et al, 2005;Luo et al, 2006;Miyake et al, 2007). This method was also used to detect EGFR mutations in NSCLC (Nagai et al, 2005;Soh et al, 2006;Sutani et al, 2006;Tanaka et al, 2007;Miyanaga et al, 2008).…”
mentioning
confidence: 99%
“…Soh et al (38) and Gow et al (39) reported an EGFR mutation rate of 24.5% (13 out of 53) in MPEs of lung adenocarcinoma. Kimura et al (40) found a 13% (3 out of 23) EGFR mutation rate by direct sequencing of EGFR mutations in MPEs of lung adenocarcinoma, of which 9.1% (1 out of 11) were females and 10% (1 out of 10) were never smokers.…”
Section: Discussionmentioning
confidence: 98%